Prevalence of Dementia among Well-Educated Old-Age Pensioners in Parakou (Benin) in 2014 - HOUINATO, Dismand (My University, 2020)
Introduction: The number of people living with dementia is growing worldwide and most rapidly in low- and middle-income countries. Little is known about dementia in Benin. We estimated the prevalence of dementia among retired people in Parakou, a northern city in Benin, and then assessed associated factors. Methods: A cross-sectional study was performed in Parakou from July to August 2014. Participants were recruited at 2 centers, the National Center of Social Security and the Public Treasury of Benin. Participants with cognitive impairment were defined as having a low cognitive score (<7) for the brief version of the Community Screening Interview for Dementia and were invited to neurological examination. DSM-IV-TR criteria were used to diagnose dementia and the HACHINSKI score was used to differentiate dementia subtypes. A logistic regression model was performed to identify factors associated with dementia. Results: Overall, 440 retired people were included in the study. They were mainly male (92.3%) and their mean age was 64.9 ± 6.0 years. The prevalence of cognitive impairment was 7.7% (95% CI 5.2-10.2). Fourteen participants were diagnosed with dementia, representing a prevalence of 3.2% (95% CI 1.5-4.8). Alzheimer disease was the most frequent subtype (64.3%), followed by vascular dementia (21.4%). Retired people diagnosed with dementia were all men and were aged between 61 and 71 years. Most of them were living alone. The main factors associated with dementia were older age, low fruit and vegetables consumption, and living alone. Discussion: This study showed a low prevalence of dementia among retired older people in Benin. Despite this, greater attention must be given to the potential burden dementia places on families for better care, before the expected aging of the population becomes more significant.
Keywords: Benin; Dementia; Older adults; Prevalence; Retirement; Sub-Saharan Africa.